Enrique Díaz y fotografías de actualidad. (De la nota gráfica al fotoensayo) - Monroy Nasr, Rebeca (El Colegio de México, A.C., 1998)
With "Enrique Díaz and Present Phpotographies (From Graphic Notes to Photo-essays) ", the author presents part of our photographic history, as well as some aspects of its development as a form of journalism and of art. She rescues the figure of Enrique Díaz Reyna as representative of the union of graphic journalists, due to his technical, formal and conceptual traits, all of them tools with which he opened important paths and innovative graphical and aesthetic proposals. This essay presents some aspects of the graphic journalist's work in Mexico City, from the twenties to the forties. As a guide to the photographer's extensive work, the author reviews some of the proposals he made as his work became more mature: first, the graphic note, later, recreating the photo-reportage, and finally, exploring with photoessays. Thus, attention is centered particularly on Díaz Reyna's visual language, where the signs of a distinctive modernity appropriate of his time allow us to understand a substantial part of the transition towards a contemporary and  truly national photo-journalism.